Vitamin E Level In Friedreich’s Ataxic Phenotype Patients In Four Major Hospitals In Baghdad - Ahmed, Ahmed Hasan (AL-Kindy College Medical Journal, 2019)
Background: Friedreich ataxia (FRDA) is the most common form of inherited ataxia, comprising one-half of all hereditary ataxias with a carrier rate between 1 in 60 to 1 in 90 and with a disease prevalence of 1 per 29,000. It can occur in two forms the classic form or in association with a vitamin E dependent ataxia. The precise role of Vitamin E in the nervous system is unknown; An Oxidative attack is suspected to play a role in Ataxia with Vitamin E deficiency, as well as in Friedreich ataxia. Vitamin E is the major free-radical-trapping antioxidant.Objective: Theobjectives of the study is to asses vitamin E level in patients with Friedreichs ataxia phenotype in Iraqi patients.Type of the study:Cross-sectional study.Method: This study was conducted at the neuroscience hospital and Baghdad teaching hospital during the period from the 1st of November 2013 through November 2014. Forty patients with friedreich's ataxia attended in neuroscience hospital and Baghdad teaching hospital during this period; there was12 male, 20 female patients and their age range between (4-50) years.Results: Regarding the level of vitamin E in patients in the present study, The study revealed that mean level of vitamin E for Friedreich ataxia patients was (10.92 μg/ml) ranging from (8-18 μg/ml),while in the control group the mean was (28.06μg/ml) ranging from (22-36μg/ml), the difference in mean level was found to be statistically significant (p=0.0001.) Thirty percents of (FRDA) patients was (8-9.9μg/ml), while half of patients (50%) were within (10-11.9 μg/ml),and low percentage (15 %)of patients were within (12-13.9 μg/ml ). The rest (5%) were had vitamin E level equal or more than 14 μg/ml. these finding revealed that majority of Friedreich ataxia patients were found with low level of vitamin E (32 patients(80%)), and low percentage with normal level (8 patients(20%.)) Patients with Friedreich ataxia were found to have a comparable level 10.47±1.79(8.4-13.5),11.48±2.61(9.4-18) and 10.66±1.26(9-12.5) for those with less than 10 years, 10-19 years , equal or more than 20 years of age respectively (p=0.382), while it was found to have a significantly decreasing level with advance in the age for the control group, 30.57±4.61(24.5-36), 27.46±3.16(23.7-33.5), 25.50±3.03 (22.9-29) for those less than 10 years, 10-19 years, 20 years or more respectively (p=0.006.) Vitamin E level in relation to Gender showed that Friedriech ataxia male patients had significantly higher vitamin E level compared to females [12.05±2.66 (9.0-18.0) compared to 10.17±1.07 (8.4-12.0)] (p=0.003), while relation to gender in the control group was not of significant value statistically [27.08±2.90 (22.9-30.0) for male compared to 29.04±4.97 (23.7-36) for females] , p=0.136.Conclusion: In the light of the results of the present study, the following conclusions were made:  The level of vitamin E in friedreichs ataxic phenotype patients was subnormal than normal range representing 80% of the sample selected for the test.  The level of vitamin E in male patients of freidriechs ataxic phenotype patients was higher than female patients.